Studi Analisis Pemanfaatan Tenaga Listrik di Pabrik Kelapa Sawit - Aris Prabowo; Zulkarnain Lubis; Zuraidah Tharo (Jurnal Serambi Engineering, 2024)
The need for electricity in industry is very important, so a device called a boiler was created to produce electricity and water steam. Boilers are a profitable choice to achieve the goal of meeting the increasing energy demand while fuel reserves are getting scarcer by the day, as well as high safety requirements, especially in industry, so in this case, research was conducted on the use of electric power for palm oil mills at PT. Serdang Jaya Perdana in processing palm oil shells and fibres, which are then used as fuel in boiler stations. From the results of the research conducted on the total electricity consumption for the palm oil production process at PT. Serdang Jaya Perdana is 650 kW/day. The highest efficiency is found at the thresher station, where the efficiency of the use of electrical energy reaches 90%. Meanwhile, the lowest efficiency was at the clarification station, which reached 77%. An optimal increase in production capacity can increase the efficiency of electrical energy use. The estimated Rupiah to be spent to use palm husk as fuel is 1062 kg/hour = 25,500 kg/day, so for one month it reaches 765,000 kg/month, so it can be converted to Rp. 688,500,000/month.